Science Literacy Among Students of Madrasah Ibtidaiyah Based on Gender and Academic Ability - Lukmana, Dana; Maulida, Ulfa (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The lack of portraits of science literacy in elementary school students has become the main reason for this study. In addition, the latest literature review shows that not all factors suspected of influencing science literacy have been studied empirically. Therefore, this study aims to describe and analyze the differences in science literacy abilities of elementary school students based on academic ability. Participants involved in this study were 88 students from a number of elementary schools in Ternate City who were selected using stratified cluster sampling. Two research instruments were used, namely the academic ability test designed to be equivalent to final semester assessment questions (PAS) that focused on science content and a set of questions to measure science literacy abilities, most of which were adapted from Xiaoping Gu. The Two-Way ANOVA was used to analyze the hypothesis, which began with normality and homogeneity tests. The findings show that partially there are differences in the science literacy abilities of elementary school students in Ternate City based on gender (Sig.0.02<0.05) and academic ability (Sig.0.001<0.05). However, the interaction of the two factors was not confirmed to determine students' science literacy abilities (Sig.0.147>0.05). This means that changes in science literacy abilities influenced by gender do not depend on the level of student's academic abilities. Likewise, the increase in science literacy scores caused by academic abilities does not depend on gender.